The Diffusion Process of The Vaccination Program Covid-19 in Order To Influence Changes in Public Attitudes Towards The Covid-19 Vaccination Program - Maman Sulaeman; Guntur F Prisanto (Blantika: Multidisciplinary Journal, 2023)
The existence of the Covid-19 pandemic has had an impact on various sectors of life such as the social, economic, cultural, health and political sectors. For this reason, the government has resolved the Covid-19 pandemic problem by issuing innovations in the form of a mass Covid-19 vaccination program. But unfortunately there is community resistance to the implementation of the program. The aim of this research is to provide an analysis of people's rejection of the Covid-19 vaccine. Research uses the theory of innovation diffusion. The research uses a qualitative descriptive approach, with a constructivism perspective paradigm, the respondents are the people of Depok city. Based on the results of the analysis it was found that there are 4 main elements that influence each other so that they can help increase the speed of innovation spread and adoption. The results of the study can be concluded that innovation in the form of Covid-19 vaccination can be effective by using the right communication channels and involving public figures, so that the messages conveyed are in accordance with the values that exist in society. The spread of innovation and adoption can go well because of the right public communication strategy. Based on the findings of this study, the authors recommend that the government be able to produce effective communication policies to reduce public resistance to the implementation of the Covid-19 vaccination.